The Relationship Between Body Mass Index and Pain Severity in Patients with Knee Osteoarthritis at Buleleng Regional General Hospital (RSUD Buleleng): Hubungan Indeks Massa Tubuh Dengan Derajat Nyeri Pada Pasien Osteoarthritis Genu Di Rsud Buleleng - I Komang Trio Cahyadi; Putu Adi Suputra; Made Budiawan (Jurnal Kolaboratif Sains, 2026)
Osteoarthritis (OA) is a prevalent joint disease marked by morning stiffness, crepitus, and pain during movement, and it represents a major cause of disability among older adults worldwide. Body mass index (BMI) has been identified as an important factor associated with pain severity in patients with knee osteoarthritis. This study aimed to examine the relationship between body mass index and pain intensity in individuals with knee osteoarthritis. A cross-sectional study design was employed involving 50 participants who fulfilled the inclusion and exclusion criteria, consisting of 22 men and 28 women. Body mass index was assessed using standardized measurements of body weight and height, while pain intensity was evaluated using the Numeric Rating Scale (NRS). The association between BMI and pain severity was analyzed using Spearman’s rank correlation test. The findings demonstrated a statistically significant positive correlation between body mass index and pain intensity in patients with knee osteoarthritis, with a moderately strong correlation (p < 0.001; r = 0.549).